2022
DOI: 10.3390/life12111867
|View full text |Cite
|
Sign up to set email alerts
|

Genital Microbiota and Outcome of Assisted Reproductive Treatment—A Systematic Review

Abstract: The balance between different bacterial species is essential for optimal vaginal health. Microbiome includes the host genome along with microorganism genomes and incorporates the biotic and abiotic factors, reflecting the habitat as a whole. A significant difference exists in the composition and number of the human microbiota in healthy individuals. About one-tenth of the total body microbiota exists in the urogenital tract and these can be identified by microscopy and culture-based methods, quantitative PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Notably, the presence of Bifidobacterium, Prevotella, and Lactobacillus iners in the vagina, along with Solanum torvum, Fusobacterium, and Streptococcus in the cervix, exhibits a negative association with successful pregnancy following in vitro fertilization. [56][57][58] The notion that the vaginal, cervical, and endometrial microbiome affects fertility is gaining support. The transfer of frozen embryos allows optimal endometrial preparation, adapting the transfer at the exact moment to favor implantation.…”
Section: Fertility Complications and The Lower Reproductive Tract Mic...mentioning
confidence: 99%
“…Notably, the presence of Bifidobacterium, Prevotella, and Lactobacillus iners in the vagina, along with Solanum torvum, Fusobacterium, and Streptococcus in the cervix, exhibits a negative association with successful pregnancy following in vitro fertilization. [56][57][58] The notion that the vaginal, cervical, and endometrial microbiome affects fertility is gaining support. The transfer of frozen embryos allows optimal endometrial preparation, adapting the transfer at the exact moment to favor implantation.…”
Section: Fertility Complications and The Lower Reproductive Tract Mic...mentioning
confidence: 99%
“…For example, the endometrial microbiota is thought to consist of 30%–70% Lactobacillus and other bacteria such as Gardnerella , Bifidobacterium , Flavobacterium , Pseudomonas , Streptococcus , Prevotella , and Atopobium , which vary dependent on the populations [ 128 , 134 , 142 , 143 ]. Some studies have indicated that the cervical and endometrial microbiomes might be involved in ART outcomes, influencing the implantation of embryo and fetal development [ 20 , 21 ].…”
Section: Reproductive Tract Microbiome and Artsmentioning
confidence: 99%
“…The increase of progesterone forms an LD community in FRT, which not only increases the production of lactic acid, but also down-regulates the expression of TLR4, suppressing inflammatory responses in cervicovaginal epithelial cells [ 75 , 156 ]. The LD community in FRT at early pregnancy can be a beneficial factor in preventing fetal rejection during ART [ 20 , 21 ]. In contrast, the NLD community is frequently associated with extensive inflammatory responses, leading to embryo transfer failure in many ART cases [ 20 , 21 ].…”
Section: Reproductive Tract Microbiome and Artsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infertility can be caused by different factors in males, females, and can be combined or even unexplained [ 3 ]. Common causes in females are diseases of the ovaries, fallopian tubes, uterus, endocrinal, genital tract dysbiosis or combined, and differ from country to country [ 5 ]. Similarly, the cause can commonly be obstruction of the tract, testicular failure of spermatogenesis, poor sperm quality, or endocrinal in males [ 3 ].…”
Section: Introductionmentioning
confidence: 99%